Red, white, and blue : a critical analysis of constitutional law - Tushnet, Mark, 1945- (Constitutional thinking., 2015)
The first paperback edition of a classic of American constitutional theory. The book is divided into two parts. In Part I Professor Tushnet appraises the five major competing ""grand theories"" of constitutional law and interpretation, and, argues that none of them satisfy their own requirements for coherence and judicial constraint. In Part II the author offers a descriptive sociology of constitutional doctrine and raises critical questions as to whether a grand theory is necessary, is it possible to construct a coherent, useful grand theory, and is construction of an uncontroversial grand th.